Zakat Effect on Aggregate Consumption in Islamic Economy in Cirebon - Risdianto (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Zakat is a tax collected from Muslim rich people to help the poor Muslim community . Results of research conducted at BAZNAS Cirebon shows that the effect of zakat can have an effect on aggregate consumption. The MPC (Marginal Propensity to Consume) value obtained for muzakki is 0.46 and mustahik is 0.76. It shows that the mustahik MPC is greater than the muzakki MPC, meaning that there is an increase in aggregate consumption due to the large change in mustahik's income. Wealthy groups who pay zakat are more stable than other rich groups who do not pay zakat, this can be seen when the income of muzakki and other rich groups is the same, the MPC values are different , namely MPCZ = 0.4 and MPCK = 0.7 . The value of MPCZ muzakki (zakat) is closer to zero than MPCK muzakki (non-zakat) which is close to one, meaning that the consumption of muzakki (zakat) is more stable. This shows that the increase in aggregate consumption in the Islamic economy is better than the conventional economy.